STUDIES IN MARINE GEOPHYSICS AND UNDERWATER SOUND FROM DRIFTING ICE STATIONS - Hunkins, Kenneth (1968)
Contents: Operations at Flectcher's Ice Island (T-3) and work at Lamont; Underwater sound; (Long-range propagation experimental work). See also report dated 1967, AD0656922.